Enforcement agent - Bodiroga Nikola (Zbornik Radova: Pravni Fakultet u Novom Sadu, 2011)
After severe discussions and almost eighty years of court-based enforcement the legislator decided it was time for a change. New Serbian Enforcement and Security Act has established enforcement agents as new legal profession. New Law distinguishes between (private) enforcement agents and court bailiffs. Only graduate and experienced lawyer who has passed special exam and meets other conditions can be appointed as enforcement agent. His primary duty is to carry the enforcement out, but in some situations he is solely responsible for the whole enforcement procedure. When it comes to collection of utilites (state companies are enforcement creditors) enforcement procedure is almost completely in hands of enforcement agent. The system of enforcement agents is not organized in a way that fosters competition. It is closed system that leads to monopoly and possible corruption. Enforcement agents are primarily responsible to the Ministry of Justice, and not so much under the court's supervision. Chamber of enforcement agents is not completely autonomous but under control of the Ministry of Justice. Besides enforcement agents court bailiffs still continue to exist. Mixture of enforcement agents and court bailiffs exists in other countries as well. Mixed status is transitional before moving to a fully private status of enforcement agents.